Dwelling Into the Realm of Self-Regulated Learning within Students Stories in Extensive Reading Activities - Bimo Teguh Prasetyanto; Nur Arifah Drajati; Ellisa Indriyani Putri Handayani (EDULANGUE, 2021)
This research aimed to discover students’ choice of actions of self-regulated learning in doing Extensive Reading (ER) activities. It also attempted to describe students’ experiences from their perspective on their self-regulated learning capability. Three students in English Education Department aged early 20s who had finished their ER course were interviewed, and their narratives were taken as the data of the research. Their stories were garnered to provide insights on how they regulated themselves in the ER activities and how they perceiveed their the experiences. The findings of this study showed that students with different levels of self-regulated learning capability chose different actions in response to the ER activities. Overlaps and development of action choices could occur among students despite their unique and different self-regulated learning capabilities. The last phase of self-regulated learning also had crucial effects on the students’ self-regulated learning capability.